Relationship between body size and milk production: A pre-study of developing village breeding centre of Etawah Crossbred goats in Yogyakarta - Suranindyah, Yustina Yuni; Utomo, Ristianto; Ismaya, Ismaya; Rihastuti, R. A.; Putri, Patricia Dwi (Kanchanaburi Rajabhat University, 2012)
The purpose of this study is to determine the relationship of body size and milk production of Etawah crossbred goats as part of selection criterias for improving female goats as breeding stock in the village. The study was conducted in the villages of Gerbosari, Samigaluh, Kulon Progo and Girikerto, Turi, Sleman, Yogyakarta, used 60 lactating goats raised under smallholder management. The goats were separated into two groups (30 animals per group) based on age. Group I consisted of 1 to 2 years and group II was older than 2 years old. The data consisted of body size (body length, heart girth, height at wither), the size of ear (length and width), udder volume and milk production were taken 2 to 3 months after kidding time. The data were statistically analysed by t-test and correlation. The results showed a significant correlation of heart girth and udder volume as well as udder volume and milk production. The equation of regression (Y) = - 785 + 13.23 X, (r2 = 0.16) for goat in group I and Y = -1331.71 + 20.79 X, (r2 = 0.24) for group II. Y is udder volume and X is heart girth. Body size and udder volume increased with advance of age and parity. The goat samples majority have funnel shape udder 40 to 63% of total number. The study concluded body size, especially heart girth, udder shape and size could be involved as criterias to select characteristic of milk production of Etawah Crossbred goat.